2019
DOI: 10.30743/ll.v3i1.1082
|View full text |Cite
|
Sign up to set email alerts
|

Thematic Progression Patterns of Short Story the Black Cat

Abstract: This study attempts to investigate thematic progression deployed in The Black Cat short story. The objectives of study are 1) To indicate the types of Thematic Progression in “The Black Cat” short story and 2) to describe the realization of Thematic Progression in “The Black Cat” short story. This study was conducted in descriptive qualitative design. The data were taken from the text of “The Black Cat” short story. The source of the data in this study was The Black Cat and Other Stories book written by Edgar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 2 publications
0
9
1
Order By: Relevance
“…Based on the above analysis of the text in three paragraphs, there is linearity between themes and rhemes in all the sentences keeping cohesion and coherence of continuous, sequence information (Hoek, 2018;Trevisan & García, 2019;Fatmawati et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the above analysis of the text in three paragraphs, there is linearity between themes and rhemes in all the sentences keeping cohesion and coherence of continuous, sequence information (Hoek, 2018;Trevisan & García, 2019;Fatmawati et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The segment of enacting intra-clauses is the base of texts' development in which these models are frequently employed to achieve discourse quality (Dong et al 2016). In detail, this thematic development is viewed as realizing the conception of textual meaning where the theme and rheme as the point of analysis (Fatmawati et al, 2019).…”
Section: Thematic Progressionmentioning
confidence: 99%
“…To deliver an authentic report, the researcher reviewed both scientific journal's papers to strengthen the concept of this study, they were simultaneously reported how the models of thematic progression used as the main analysis to help the learners write their ideas clause by clause. First publication came from Fatmawati et al (2019) where this study focused on the analysis on the story of "The black cat" by means of the pattern of thematic progression. They referred to the theory that was proposed by Halliday (1994), and the findings qualitatively showed that constant theme was the most applicable in this analysis that employed in this story.…”
Section: Introductionmentioning
confidence: 99%
“…There are two previous researches done by Fatmawati (2019) and Muthoharoh (2014) that helped the writer to better understand thematic progression. These previous researches used descriptive qualitative as their method and both analyzed the kind of thematic progression used on their research object.…”
Section: Introductionmentioning
confidence: 99%